Overcoming Destructive Anger : Strategies that Work - Golden, Bernard (John Hopkins University Press, 2016)
Readers will be drawn to this books because their lives have been affected, even devastated , by anger. Job loss, divorce, family estrangement, substance abuse, and imprisonment are just some of the potential fallouts from uncontrolled anger.Many pero